Correlational study of psychological variables self-confidence and anxiety - Gloria González Campos; Javier Cachón Zagalaz; Santiago Romero Granados (Universidade Estadual Paulista (UNESP), 2015)
Abstract The purpose of this study is to analyze the concurrent validity of the psychological variables self-confidence and anxiety among the psychological measurement instruments: Psychological Characteristics Questionnaire related to Sports Performance (CPRD); Competitive State Anxiety Inventory-2 (CSAI-2); and Sports Psychological Inventory LOEHR. For this purpose, a correlational study was conducted between the selected variables and pertinent aspects of the measurement instruments. The study has revealed that the psychological variables self-confidence and anxiety are relevant in all three instruments, although not in all of the selected items.